First record of the invasive land flatworm Bipalium adventitium (Platyhelminthes, Geoplanidae) in Canada - Justine, Jean-Lou; Théry, Thomas; Gey, Delphine; Winsor, Leigh (Zootaxa, 2019)
Specimens of Bipalium adventitium (Platyhelminthes, Geoplanidae) were found in Montréal, Québec, Canada. The specimens showed the typical colour pattern of the species and barcoding (Cytochrome Oxidase I) demonstrated near-identity with a sequence of the same species from the USA. This is the first record of the species in Canada.